Breed, sex, and litter effects in 2-month old puppies’ behaviour in a standardised open-field test - Shanis Barnard (Nature Portfolio, 2017)
Abstract A considerable number of studies have reported differences among dog breeds with respect to their genetic profile, cognitive abilities or personality traits. Each dog breed is normally treated as a homogeneous group, however, researchers have recently questioned whether the behavioural profile of modern breeds still reflects their historical function or if the intense divergent selective pressures and geographical barriers have created a more fragmented picture. The majority of studies attempting to assess and compare modern breeds’ personality focused on the evaluation of adult dogs where the potential effects of environmental/human factors on the dogs’ behaviour are hard to discern from their genetic heritage. In the following study, we aimed at investigating between- and within-breed differences in the personality of two-months-old puppies by direct behavioural observation of 377 puppies from 12 breeds. Results showed that there was no effect of sex, however both breed and litter, significantly affected all personality traits. Breed on average explained 10% of the variance, whereas the effect of litter was noticeably higher, explaining on average 23% of the variance. Taken together, our results suggest that breed does have some influence on personality traits, but they also highlight the importance of taking litter effects into account.